Phytochemical Profiles and Biological Activities of Frankenia Species: A Review - Meyada Khaled; Rachid Ouache; Patrick Pale; Hassina Harkat (Molecules, 2024)
The relatively small Frankeniaceae family is represented by halophyte plants, growing in arid and semi-arid climates in saline, alkaline or calcareous soils. Due to their living conditions, they usually produce a large diversity of compounds, which often exhibit bioactivities. Some species of this genus have long been used as traditional herbal medicines to treat dysentery, diarrhea, gonorrhea, vaginal leucorrhea, respiratory diseases and wounds. To date, several studies on either phytochemical or pharmacological aspects, or both, have revealed that this genus is a rich source of diverse and novel bioactive chemicals, including phenolics, flavonoids, alkaloids and fatty acids. This review describes all the reported chemical profiles of Frankenia species, as well as the corresponding biological properties, when available. The aim of this review is to show the potential of these plants for various applications, especially therapeutic ones.